2023
DOI: 10.1101/2023.09.26.559520
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The structural landscape and diversity ofPyricularia oryzaeMAX effectors revisited

Mounia Lahfa,
Philippe Barthe,
Karine De Guillen
et al.

Abstract: Plant pathogenic fungi secrete a wide variety of small proteins, named effectors.MagnaportheAVRs and ToxB-like (MAX) effectors constitute a superfamily of secreted proteins widely distributed inPyricularia (syn. Magnaporthe) oryzae, a devastating fungus responsible for blast disease in cereals such as rice. In spite of high evolutionary sequence divergence, MAX effectors share a common fold characterized by a ß-sandwich core often stabilized by a conserved disulfide bond. In this study, we investigated the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…MAX effectors are massively and specifically expressed during early biotrophy (de Guillen et al., 2015 ; Le Naour‐Vernet et al., 2023 ; Yan et al., 2023 ). They include many AVR proteins recognized by intracellular NLR immune receptors (Lahfa et al., 2023 ). Additional structural families of P. oryzae effectors have been identified by genome‐wide modelling of protein structures (Derbyshire & Raffaele, 2023 ; Seong & Krasileva, 2021 ; Seong & Krasileva, 2023 ).…”
Section: Molecular Mechanisms Governing the Life Cyclementioning
confidence: 99%
“…MAX effectors are massively and specifically expressed during early biotrophy (de Guillen et al., 2015 ; Le Naour‐Vernet et al., 2023 ; Yan et al., 2023 ). They include many AVR proteins recognized by intracellular NLR immune receptors (Lahfa et al., 2023 ). Additional structural families of P. oryzae effectors have been identified by genome‐wide modelling of protein structures (Derbyshire & Raffaele, 2023 ; Seong & Krasileva, 2021 ; Seong & Krasileva, 2023 ).…”
Section: Molecular Mechanisms Governing the Life Cyclementioning
confidence: 99%
“…Gene annotation investigation successfully identified 58 to 78 MAX effector genes per genome in a set of 120 isolates representing seven host-associated lineages leading to restriction of early biotrophic infection and strongly influenced by the host plant . NMR observation shown that MAX effectors superfamily in 20 structural groups that vary in the canonical MAX fold, disulfide bond patterns, and additional secondary structures in N-and C-terminal extensions which potentially effecting the wide diversity of their virulence functions and host targets (Cadiou, et al, 2023;Lahfa et al, 2023).…”
Section: Blast Disease Intensity On Leaves (%)mentioning
confidence: 99%